PHYSICIANS' AND HEALTHCARE SPECIALISTS' BEHAVIOR TOWARDS THEIR OWN HEALTH - Natalia Shtereva-Nikolova; Radka Goranova-Spasova; Emilia Naseva; Neli Gradinarova; Magdalena Aleksandrova (Peytchinski Publishing, 2018)
Healthcare professionals are expected to be committed to the profession and patients, competent, high-performing and always healthy. But being a physician and a healthcare specialist is also a great challenge. The purpose of this article is to investigate physicians' and healthcare specialists' behavior towards their own health. Methodology - a direct and anonymous survey was carried out with a specially designed questionnaire. The medical and social significance of physicians' and healthcare specialists' behaviour had been investigated. The study was conducted in June / July 2018 among 109 workers (46 physicians and 63 healthcare professionals). Results and Discussion - 31.2% of respondents said they attended at least once their general practitioner and 27.5% - not at all for the last year. 51.4% reported that they had been sick with differences between healthcare specialists and physicians. We found out that only 21.1% had a sickness absence and there was no statistically significant gender difference. From the analysis of the outcomes, we observed that 15.2% of physicians confirm the sick leave due to illness, and about a quarter of the healthcare specialists answered similarly. Conclusion: From the study of the problem, we founded that healthcare workers ignore their physical, emotional and social condition. It is important to encourage them to take time to rest, to cure their illnesses and, last but not least, to be an example for other employees and patients.